A compact triband microstrip antenna utilizing hexagonal CSRR for wireless communication systems - Murtala Aminu- Baba; Mohamad Kamal A. Rahim; Farid Zubir; Mohd Fairus Mohd Yusoff; Adamu Y Iliyasu; Mohammed Mustapha Gajibo; Huda A. Majid; K. I Jahun (Institute of Advanced Engineering and Science, 2020)
In this paper, a compact triband printed antenna with hexagonal complementary split-ring resonators (CSRRs) for 4G applications is proposed. The proposed multiband antenna is comprised of a rectangular patch antenna on the top plane, while on the ground plane, hexagonal CSRRs are etched for size miniaturization (at the lower bands) and multiband generation. Another effect of the CSRR is the shifting of the initial resonance of the patch antenna from 5.17 GHz to the higher band of 6.18 GHz. The triband of 180 MHz 2.4 2.59, 150 MHz 2.79 2.94 and 420 MHz 6.04 6.46 GHz bands acquired can cover WLAN/Wi-Fi and WiMAX operating bands adequately. This can be achieved by choosing the optimal size and position of the CSRR on the ground plane carefully. The design occupies a total size of 45 x 45 mm2 using the low-cost FR-4 substrate. Good agreements are obtained between the measured results and the simulated, which are discussed and presented.